THE IMPACT OF AI ON HUMAN TRANSLATION: COMPLEMENT OR COMPETITION? - Shahnoza Dusmamatovna Razakova (Modern American Journals, 2025)
This article explores the impact of artificial intelligence on human translation, focusing on whether AI serves as a complement to or a competitor against professional translators. The rapid development of neural machine translation systems, large language models, and adaptive algorithms has transformed the field of translation, making it necessary to reconsider the role of human expertise in the process. The study emphasizes the dual nature of AI in translation: on the one hand, it provides unprecedented speed, accessibility, and efficiency in handling multilingual content; on the other hand, it raises concerns about accuracy, cultural sensitivity, and the potential displacement of human translators. The research highlights how AI translation tools are currently applied in academic, professional, and everyday contexts, and examines the extent to which they meet the requirements of precision and contextual awareness demanded in specialized fields, such as pedagogy and linguistic education. By analyzing the strengths and limitations of AI translation technologies in comparison with human translation, the article demonstrates that AI is not merely a substitute for human translators, but also an instrument that can enhance their productivity when used strategically. The findings suggest that the future of translation will most likely be characterized by a hybrid model, where AI handles routine tasks and human translators provide critical evaluation, stylistic refinement, and cultural adaptation. The study concludes that understanding the relationship between human and AI translation is essential for shaping the future of language education, intercultural communication, and translation studies.
Keywords: Artificial intelligence, human translation, machine translation, pedagogy, intercultural communication, language education, digital transformation, translation studies, linguistic accuracy, neural networks